Decrease in APP and CP mRNA expression supports impairment of iron export in Alzheimer's disease patients - Guerreiro, Cláudia (2015)
Alzheimer's disease (AD) is a neurodegenerative disorder of still unknown etiology and the leading cause of dementia worldwide. Besides its main neuropathological hallmarks, a dysfunctional homeostasis of transition metals has been reported to play a pivotal role in the pathogenesis of this disease. Dysregulation of iron (Fe) metabolism in AD has been suggested, particularly at the level of cellular iron efflux. Herein, we intended to further clarify the molecular mechanisms underlying Fe homeostasis in AD. In order to achieve this goal, the expression of specific Fe metabolism-related genes directly involved in Fe regulation and export was assessed in peripheral blood mononuclear cells (PBMCs) from 73AD patients and 74 controls by quantitative PCR. The results obtained showed a significant decrease in the expression of aconitase 1 (ACO1; P=0.007); ceruloplasmin (CP; P<0.001) and amyloid-beta precursor protein (APP; P=0.006) genes in AD patients compared with healthy volunteers. These observations point out to a significant downregulation in the expression of genes associated with ferroportin-mediated cellular Fe export in PBMCs from AD patients, when compared to controls. Taken together, these findings support previous studies suggesting impairment of Fe homeostasis in AD, which may lead to cellular Fe retention and oxidative stress, a typical feature of this disease